الحماية الاجتماعية في الإسلام مدى فاعلية أنظمة الضمان الاجتماعي المعاصرة في تحقيق العدالة الاجتماعية: دراسة مقارنة: Social protection in Islam- the effectiveness of contemporary social security systems in achieving social justice: Comparative study summary - محيوتي عاشور; بن منصور عبد الله (Journal of North African Economies, 2025)
The Islamic civilization has taken care of the affairs of the Islamic state and Muslim and non-Muslim citizens who are in its surroundings and covered by its care, so that security and social peace prevail among them, which sets solid rules of relations between Muslims and others, and this should fall within the general policy of countries in order to achieve a promising future for societies and individuals, and more equal, and this research aims to study the effectiveness of social security systems contemporary and compared to the social protection system in Islam, by presenting the foundations and manifestations of Islamic law care for the poor and needy in society and achieving social justice, and identifying similarities and differences between contemporary social security systems, and social protection provided by the Islamic religion, the study concluded a result represented in the precedence of the Islamic religion for the process of devoting social protection by targeting the poor and needy groups in providing them with sufficiency, and that work in Islam is a priority in providing the needs of individuals in society before asylum to others through the mechanism of social solidarity, which comes when necessary and in the second degree.